Gonad Maturity of Coconut Crab (Birgus latro) in Pasoso Island, Central Sulawesi - . Sulistiono; Suzana Refiani; Fadly Y. Tantu; . Muslihuddin (Jurnal Akuakultur Indonesia)
Study on gonad maturity of coconut crab (Birgus latro) was carried out from June 2004 to January 2005.  Crabs were collected by some gears such as trap, net and by hand. Observation was done to know sex ratio, gonad maturity and eggs diameter, while analysis was employed to estimate condition factor, gonado somatic index and fecundity.  Observation result showed that condition factor, gonad maturity and gonado somatic index varied depending on sampling month. Gonado somatic index showed a high value around November/December.  A similar result was also showed by condition factor and gonado somatic index that was high around November /December. Fecundity varied from 58.717 to 197.400. Oocyte diameter varied from 0,015 to 0,035 mm,  had one mode that is clasified to be a total spawner.